“WHAT BINDS YOU TOGETHER AS WOMEN?”: SEX EDUCATION’S SEXUAL ASSAULT STORYLINE AS A #METOO NARRATIVE - Salinas Torres, Belén (Filanderas, 2024)
This article delves into the didactic potential of the sexual assault storyline found in the second season of Sex Education (Nunn, 2019-2023). Specifically, it examines how this narrative facilitates the recognition of such traumatic experiences and portrays an ideal response of sorority through a liberal feminist lens, echoing the #MeToo movement within the context of fourth-wave feminism. To this end, the essay analyses the evolution of cinematic representations of sexual violence over time, focusing on its current depiction after the ignition of the #MeToo movement. Subsequently, an analysis of the five-episode storyline explores the trajectory of trauma, from its actual perpetration until the point when the victim/survivor begins her healing journey, emphasising the long-time impact of the aggression and its psychological consequences. The essay concludes that this process demands the victim to redefine her identity, representing an empowerment quest towards a more educated, aware, and multi-faceted version of herself.